IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DALAM MENANGGULANGI KEMISKINAN DI DESA KAMPUNG MESJID KECAMATAN KUALUH HILIR KABUPATEN LABUHAN BATU UTARA - Akbar, Fadillah Aulia; Lubis, Khairunnisah; Sinaga3, Rudi Salam (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to analyze the implementation of the Family Hope Program (PKH) in alleviating poverty in Kampung Mesjid Village, Kualuh Hilir Subdistrict, Labuhan Batu Utara Regency. The study employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation, involving key informants such as the village head, PKH officers, and program beneficiaries. George C. Edward III's implementation theory was used as the analytical framework, focusing on communication, resources, disposition, and bureaucratic structure. The results show that the implementation of PKH in Kampung Mesjid Village has had a positive impact, particularly in improving access to education and healthcare for poor families. However, several challenges remain, including inaccurate beneficiary data, limited resources, and the apathetic attitude of some program participants. This study provides recommendations to enhance program effectiveness, including optimizing data collection, improving human resource capacity, and strengthening communication among stakeholders.